A Comparative Study Between Darrach and Sauvé-Kapandji Procedures for Post-Traumatic Distal Radioulnar Joint Dysfunction. (May 2021) - Verhiel, Svenna H. W. L.; Özkan, Sezai; Ritt, Marco J. P. F.; Chen, Neal C.; Eberlin, Kyle R.
Background: There are various treatments for post-traumatic distal radioulnar joint (DRUJ) dysfunction. The present study aimed to assess differences in long-term patient-reported outcomes on physical function, pain, and satisfaction between the Darrach and Sauvé-Kapandji procedures. Secondary aims were to describe the radiographic outcomes and to assess the difference in rate and type of complications and reoperations between these 2 procedures.Methods: We retrospectively analyzed 85 patients who had a post-traumatic DRUJ derangement and had been treated by either a Darrach (n = 57) or Sauvé-Kapandji procedure (n = 28). Fifty-two patients (61%) completed patient-rated outcomes surveys at a median of 8.4 years after their procedure. Radiographic measurements consisted of ulnar distance, radioulnar distance, and ulnar gap (only in Sauvé-Kapandji group).Results: There were no significant differences in Patient-Reported Outcomes Measurement Information System (PROMIS) Upper Extremity (UE) Function score, pain score, satisfaction score, complications, and reoperations between patients who had a Darrach procedure or a Sauvé-Kapandji procedure. Seventeen patients (30%) in the Darrach group experienced a complication, and 14 patients (50%) in the Sauvé-Kapandji group experienced a complication ( P = .09). The most common complication was instability of the ulnar stump (n = 10), followed by symptoms of the dorsal sensory branch of the ulnar nerve (n = 8). Patients who underwent a Sauvé-Kapandji procedure had more reoperations for excision of heterotopic ossification.Conclusions: Darrach and Sauvé-Kapandji procedures show comparable long-term patient-reported outcomes in treatment of post-traumatic DRUJ dysfunction. Complication and reoperation rate are relatively high, with non-significant differences between the 2 procedures.